Emotional labor and empathic concern as predictors of exhaustion and disengagement in college teachers - Xiaohui Zhai; Shazia Rehman; Abdullah Addas; Qingke Liu; Erum Rehman; Muhammad Nasir Khan (Scientific Reports)
Abstract Emotional labor has been widely studied in organizational settings, but its impact on job burnout, particularly within educational contexts, remains underexplored. This study examines how emotional labor influences the distinct dimensions of job burnout—exhaustion and disengagement—with empathetic concern as a potential mediator and gender as a moderating factor. In this cross-sectional study conducted in both private and public colleges in Rawalpindi, Pakistan, data was collected from 1,128 college teachers using three validated scales: the Oldenburg Burnout Inventory (OLBI) to assess burnout, the Emotional Labor Questionnaire (ELQ) for emotional labor, and the Interpersonal Reactivity Index (IRI) to evaluate the empathic concern. A path mediation analysis was employed to investigate the study hypotheses and explore the relationship between emotional labor, empathic concern, and burnout among college educators. Additionally, gender was examined as a moderating variable to assess whether the impact of emotional labor on burnout differed across male and female teachers. Emotional labor significantly predicted both exhaustion (β = 0.414, p < 0.001) and disengagement (β = 0.302, p = 0.003). Empathetic concern significantly mediated the relationship between emotional labor and exhaustion (indirect effect = 0.090, 95% CI = 0.03–0.125) but not between emotional labor and disengagement (indirect effect = 0.020, 95% CI = -0.010–0.060). Gender was found to significantly moderate the relationship between emotional labor and exhaustion (interaction effect = 0.133, 95% CI: 0.035 to 0.225), indicating that this association varies across male and female teachers, while no moderation effect was observed for disengagement. The significant mediation effect observed for exhaustion, but not disengagement, suggests that different strategies may be needed to address these distinct aspects of burnout. Additionally, the moderating role of gender in the emotional labor–exhaustion relationship highlights the importance of considering demographic factors when designing well-being interventions. These findings have important implications for developing targeted support strategies for teachers, particularly within the cultural context of Pakistan. Further research is needed to explore these dynamics over time and across different educational environments.